2003
DOI: 10.1183/09031936.03.00054202
|View full text |Cite
|
Sign up to set email alerts
|

Single arterial occlusion to locate resistance in patients with pulmonary hypertension

Abstract: The purpose of this study was to determine the site of increased resistance using the arterial occlusion technique in patients with severe pulmonary hypertension.Pulmonary vascular resistance was partitioned in arterial and venous components based on double exponential fitting analysis of the pulmonary artery pressure decay curve: after balloon occlusion in 36 patients with pulmonary arterial hypertension (PAH); at baseline and during the inhalation of 20 parts per million of nitric oxide (NO); in four patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 35 publications
(43 reference statements)
3
42
0
Order By: Relevance
“…A separate, blinded investigator performed a biexponential fitting of the pressure decay curve between the moment of occlusion and the PAOP, with normalisation to the mPAP. This has been previously described and is used here to derive occlusion pressure (Poccl) [5,8]. Rup (upstream pressure) was calculated as follows: Rup % 5 100 6 (mPAP -Poccl) / (mPAP -PAOP).…”
Section: Methodsmentioning
confidence: 99%
“…A separate, blinded investigator performed a biexponential fitting of the pressure decay curve between the moment of occlusion and the PAOP, with normalisation to the mPAP. This has been previously described and is used here to derive occlusion pressure (Poccl) [5,8]. Rup (upstream pressure) was calculated as follows: Rup % 5 100 6 (mPAP -Poccl) / (mPAP -PAOP).…”
Section: Methodsmentioning
confidence: 99%
“…The measurement of the effective Pcap requires the analysis of a PAOP decay curve after balloon occlusion through different methods: (1) the visual inspection method, where the inflection point is designated as the capillary pressure; (2) a single exponential curve is fitted to the average arterial occlusion pressure decay in the segment between 0.3 s and 2 s after time 0 (occlusion); and (3) a better fit of PAOP decay curves after balloon occlusion is obtained with a biexponential function. This method of calculation led to lower Pcap values than found using a mono-exponential fitting ( Figure 3) [6,8,11] . When the PA is occluded, there is a rapid decrease in Table 2 Recommendations for right heart catheterization blood flow as the occluded downstream PA discharges its blood volume sequentially into the pulmonary capillaries across the arterial resistance and then into the pulmonary veins across the venous resistance.…”
Section: Parametersmentioning
confidence: 89%
“…The measurement of an effective Pcap, requires the analysis of a PAP decay curve after balloon occlusion, as will be described later [8,9] . A hemodynamic study was recently conducted in 3920 patients with PH, and the reliability of PAOP to distinguish PAH and PH associated with LV disease compared to LV end-diastolic pressure (the gold standard of LV preload) was analyzed.…”
Section: Parametersmentioning
confidence: 99%
“…By definition, true capillary pressure (Pc) and measured PCWP are normal (<15 mmHg) in idiopathic PAH. Since Pc measurement is not suitable for clinical application, PCWP is currently the most frequently used method for estimating Pc in a broad range of clinical and/or experimental conditions [57,58]. By contrast, in PVOD experimental conditions, the post-capillary obstruction leads to an elevated Pc without any increase in PCPW [59,60].…”
Section: Hemodynamic Evaluation Pulmonary Capillary Wedge Pressurementioning
confidence: 99%
“…Measurement of the Pc may theoretically be useful in PVOD; the principle of Pc pressure measurement is extrapolated from a canine model whereby the pressure decay following balloon occlusion is mathematically analyzed to represent the emptying of the capillary compartment [61]. Interestingly, Fesler et al showed showed that this method helps to locate the site of predominantly increased pulmonary vascular resistance in severe PAH and that patients displaying PVOD may have higher Pc than PAH patients using this method [57,58].…”
Section: Hemodynamic Evaluation Pulmonary Capillary Wedge Pressurementioning
confidence: 99%